The impact of applying certain financial inclusion indicators on financial performance in the banking sector in Libya (Al-Farooq Journal of Sciences, 2026)
Tis study aimed to examine the impact of applying certain financial inclusion indicators on the performance of the banking sector in Libya, measured by the return on equity.                              The study sample included public and private commercial banks, and the study period extended from (2019 to 2024). The multiple regression model was used, relying on date extracted from reports and financial statements issued by the Central Bank of Libya to test the study hypothesis.The findings also indicated that there is a statistically significant positive effect of financial inclusion indicators on the financial performance of the banking sector in Libya, measured by return on equity. The study provided possible explanations for these findings, in addition to several recommendations for those responsible for the banking sector regarding the impact of applying certain financial inclusion indicators on financial performance.
Keywords: Financial Inclusion, Financial Inclusion Indicators, Financial Performance, Libyan Banking Sector